Prognostic Value of Postoperative Neutrophil and Albumin: Reassessment One Month After Gastric Cancer Surgery - Guner, Ali; Cho, Minah; Kim, Yoo-Min; Cheong, Jae-Ho; Hyung, Woo Jin; Kim, Hyoung-Il (Frontiers in Oncology, 2021)
Objective: The prognostic value of postoperative parameters reflecting the inflammatory and nutritional status of patients undergoing cancer surgery has been rarely studied. This study investigated the prognostic value of inflammatory and nutritional parameters measured preoperatively and 1-month after curative gastrectomy for gastric cancer. Methods: Data from a prospectively maintained database of 1194 patients with gastric cancer who underwent curative surgery in 2009–2018 were retrospectively reviewed. Demographics, clinicopathologic characteristics, operative data, survival data, and laboratory parameters were extracted. Neutrophil counts, lymphocyte counts, and albumin levels before surgery and 1 month postoperatively were analyzed. Results: In multivariable analysis adjusted for age, sex, and pathologic stage, high neutrophil count (hazard ratio [HR] 1.09, 95% confidence interval [CI] 1.01–1.17, p=0.022) and low albumin (HR 0.45, 95% CI 0.27–0.74, p=0.002) 1 month postoperatively were independent prognostic factors for overall survival. High neutrophil count (HR 1.09, 95% CI 1.02–1.16, p=0.015)1 month postoperatively was also an independent prognostic factor for recurrence-free survival after adjusting for age, sex, body mass index, extent of gastrectomy, and pathologic stage. Patients were classified into risk groups based on thresholds of 4.2x103 cells/mm3 and 4.1 g/dL for 1-month neutrophil count and albumin. High-risk groups had a significantly worse prognosis than low-risk groups for overall survival (HR 5.87, 95% CI 3.28–10.51, p<0.001) and recurrence-free survival (HR 1.52, 95% CI 1.07–2.16, p=0.021). Conclusions: Neutrophil count and albumin level 1 month after curative surgery predict long-term prognosis better than preoperative values. These parameters can be used to stratify patients with the same stage into different prognostic groups.